Adenosine A1 receptor antagonist mitigates deleterious effects of sleep deprivation on adult neurogenesis and spatial reference memory in rats. (19th November 2016) - Chauhan, G.; Ray, K.; Sahu, S.; Roy, K.; Jain, V.; Wadhwa, M.; Panjwani, U.; Kishore, K.; Singh, S.B.
Graphical abstract: Highlights: Sleep deprivation for 48 h causes deficits in spatial memory and adult neurogenesis. Adenosine A1R antagonist 8-CPT improve SD induced deficits in spatial memory. 8-CPT rescues adult neurogenesis during SD by modulating BDNF levels in DG and CA1 region. Abstract: Sleep deprivation (SD) upsurges intracellular levels of adenosine, impairs adult neuronal cell proliferation (NCP) and cognition while caffeine, a non-selective adenosine A1 receptor (A1R) antagonist improves cognition and adult NCP during SD. We examined the selective antagonistic effects of adenosine A1R using 8-cyclopentyl-1, 3-dimethylxanthine (8-CPT) on impairment of spatial reference memory and adult NCP during 48 h SD. Adult male Sprague Dawley rats were sleep deprived for 48 h, using an automatic cage vibrating stimulus based on animal activity. Spatial reference memory was tested as a measure of cognitive performance employing Morris Water Maze. Rats were given 8-CPT dissolved in 50% dimethyl sulfoxide (DMSO), twice daily (10 mg/kg, i.p.) along with 5-bromo-2-deoxyuridine (BrdU) (50 mg/kg/day, i.p.). The rats treated with 8-CPT showed significantly short mean latency and path-length to reach the platform compared to the SD rats. Consistent with these findings, 8-CPT-treated group was found to have significantly increased the number of BrdU, Ki-67 and doublecortin (DCX) positive cells. However, no significant difference was seen in NeuN expression in the Dentate Gyrus (DG). Brain-derived neurotropic factor (BDNF) expression in the DG and CA1 region was observed to decrease significantly after SD and be rescued by 8-CPT treatment. Furthermore, latency to reach platform showed a negative correlation with number of BrdU, DCX type-1 cells and BDNF expression in DG. Thus, it may be concluded that treatment with 8-CPT, an adenosine A1R antagonist during SD mitigates SD induced decline in spatial reference memory and adult NCP possibly via up regulation of BDNF levels in DG and CA1 regions.